Electron microscopic GABA evaluation in hippocampal mossy terminals of genetic absence epilepsy rats receiving kindling stimulations - KAYA, ÖZLEM TUĞÇE; TURGAN AŞIK, ZEHRA NUR; KARAMAHMUTOĞLU, TUĞBA; GÜLÇEBİ İDRİZ OĞLU, MEDİNE; AKAKIN, DİLEK; ŞİRVANCI, SERAP (My University, 2022)
Objective: The hypotheses related to the fact of epileptic mechanisms are mainly based on excitation-inhibition imbalance in central nervous system. GAERS (Genetic Absence Epilepsy Rats from Strasbourg) is a well-known animal model of absence epilepsy, and frequently used in experimental studies. In the present study, we aimed to examine possible morphological and gamma-aminobutyric acid (GABA) density changes in GAERS hippocampus after electrical kindling stimulations. Methods: All control and test group rats received 6 kindling stimulations. Rats were decapitated 1 h after the last stimulation. Ultrastructural GABA immunocytochemistry was used to evaluate GABA density quantitatively in mossy terminals of hippocampal CA3 region. Results: GABA levels were less in kindling groups compared to their controls, and in GAERS groups compared to Wistar groups; mitochondrial and dendritic spine area ratios were greater in GAERS groups compared to Wistar groups, although all these evaluations were statistically nonsignificant. Depletion of synaptic vesicles was evident in the mossy terminals of kindling groups. Conclusion: The reason of decreased levels of GABA found in the present study might be that GABA has been released from the synaptic pool rapidly at an early time period after the last stimulation, for compansation mechanisms. Depletion of synaptic vesicles observed in kindling groups shows that even 6 kindling stimulations have an impact of changing hippocampal morphology in trisynaptic cycle. The increased mitochondrial area in GAERS might be related to the increased mitochondrial activity. The increased dendritic spine area might be related to the increased performance of learning in GAERS. Our findings indicating that absence epilepsy and temporal lobe epilepsy have different mechanisms of epileptogenesis might be a basis for further experimental studies.
Keywords: Absence epilepsy; GAERS; hippocampus; kindling; GABA; immunocytochemistry